Effects of Solid Waste and Industrial Effluents on Water Quality of Turag River at Konabari Industrial Area, Gazipur, Bangladesh (Journal of Environmental Science and Natural Resources, 2013)
The study was conducted to investigate the effects of solid waste and industrial effluents on the water quality of Turag River. Both the upstream and downstream sampled water from the selected points were analyzed for color, odor, pH, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), copper (Cu), cadmium (Cd), iron (Fe), lead (Pb) and zinc (Zn) concentrations. Results of the study showed that the color of water was light to dark black and emitted noxious smell due to the industrial effluents. The upstream water was slightly alkaline with comparatively high DO content while low concentration of other parameters. The water after the solid waste and effluents received points as well as middle and downstream points was slightly alkaline with higher levels of other parameters when compared with upstream point. The minimum and maximum values of pH, EC, TDS, DO and BOD were 7.24-7.61, 425-2277 ?S/cm, 239-1349 ppm, 1.22-3.66 ppm and -2.44-0.86 ppm, respectively. The continuous dumping of waste materials resulted in a marked increase in the concentration of metals in the river water varied in the order of Fe > Zn > Pb > Cu > Cd. The study concluded that the downstream water in the river was almost polluted and unsuitable for human consumption and aquaculture purposes.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14817 J. Environ. Sci. & Natural Resources, 5(2): 213-218 2012